PENGARUH TRANSPARANSI DAN KINERJA TERHADAP PROFIT DISTRIBUTION : Studi Empiris Bank Umum Syariah di Indonesia periode 2010-2013 - Rensi Permatasari; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2015)
This study aims to examine transparency and performance to profit distribution of islamic bank in Indonesia. The study of Lachrech found that performance has strong correlation to profit distribution. The disclosure level of information in islamic bank is needed by investment account holder as transparency is given by islamic bank. Dependent variable used in this study is profit distribution. Independent variabels used in this study are disclosure  level of information and performace measured by CAMELS. (CAR, ASSET, MANAGEMENT, EARNINGS, LIQUIDITY. And SENSITIVITY).The sampel of this study consists all islamic bank listed on BI in year 2010 until 2013. The sampling method used in this study was purposive random sampling and content analysis. There are  43  banks that  become  sampel  of  this  study.  The  analysis  technique  used  is  the  multiple regression analysis.The results show that disclosure level of information as transparency has no significant effect to profit distribution, Performance consists of CAR, NPF, NIM has postive significant effect to profit distribution. CI has negative significant effect to profit distribution.